1996
DOI: 10.1210/endo.137.12.8940342
|View full text |Cite
|
Sign up to set email alerts
|

Induced illness in interleukin-6 (IL-6) knock-out mice: a causal role of IL-6 in the development of the low 3,5,3'-triiodothyronine syndrome.

Abstract: Interleukin-6 (IL-6) administration to human subjects or experimental animals induces changes in thyroid hormone metabolism resembling those in the sick euthyroid syndrome. Furthermore, the decrease in serum T3 during illness is significantly related to serum IL-6 concentrations. These findings suggest, but do not prove, a causal role for IL-6 in the development of the low T3 syndrome. The aim of the present study was to evaluate the role of IL-6 in the development of the sick euthyroid syndrome in IL-6 knock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 17 publications
4
35
1
1
Order By: Relevance
“…An analysis of 100 consecutive hospitalized patients revealed a weak inverse correlation between the serum levels of IL-6 and T3 (30). These data are consistent with studies in wild-type versus IL-6 null mice (31). For example, following injection of lipopolysaccharide, serum T3 fell in both wild-type and null mice, but the drop was smaller in the IL-6 null animals.…”
Section: Discussionsupporting
confidence: 80%
“…An analysis of 100 consecutive hospitalized patients revealed a weak inverse correlation between the serum levels of IL-6 and T3 (30). These data are consistent with studies in wild-type versus IL-6 null mice (31). For example, following injection of lipopolysaccharide, serum T3 fell in both wild-type and null mice, but the drop was smaller in the IL-6 null animals.…”
Section: Discussionsupporting
confidence: 80%
“…Third, the model shows that reverse T3 decreases during bacterial NTI, in contrast to the typical increase observed in patients. Previous murine studies reported that liver type I deiodinase decreases significantly between 4 and 8 h and normalizes at 24 h after LPS injection (18,19,28,29). Our reverse T3 findings suggest that type I deiodinase activity is not significantly impaired, allowing the degradation of reverse T3 to di-iodo-thyronine.…”
Section: Discussionsupporting
confidence: 50%
“…Previously, we have shown that IL-6, an important proinflammatory cytokine, is involved in alterations of the peripheral part of the HPT axis (12 mice. These differences might be due to unknown genetic differences induced by genetic manipulation or to unknown inflammation-independent effects of IL-18 on basal IFNg expression (IFNg could interfere with several mechanisms in thyrocytes (3)), because the observed differences were present in both IL-18…”
Section: Discussionmentioning
confidence: 96%